Three-dimensionally patterned Ag–Pt alloy catalyst on planar Si photocathodes for photoelectrochemical H2 evolution. Issue 8 (6th February 2019) - Lim, Sung Yul; Ha, Kyungyeon; Ha, Heonhak; Lee, Soo Youn; Jang, Min Seok; Choi, Mansoo; Chung, Taek Dong
Abstract : Three-dimensionally patterned Ag–Pt alloy catalyst improves a junction quality of electrolyte/SiO x /Si photocathodes for H2 evolution. Abstract : Platinum is still the most active element for the hydrogen evolution reaction (HER); however, it suffers from its scarcity and high cost. Thus, significant efforts have been dedicated to maximize the catalytic activity with less loading. When Pt is utilized at a semiconductor surface, more factors have to be considered. Placing a catalyst directly in contact with a semiconductor supports the extraction of photogenerated minority carriers as well as boosts the catalytic reactions. In addition, a catalyst should be designed with prudence not to interfere in the light path with respect to absorption at the underlying substrate. Herein, we report the development of planar Si-based photocathodes, covered with a native oxide, for the HER, which also satisfy the prerequisites for the use of a three-dimensionally patterned, flower-like Ag–Pt catalyst. The catalyst consisted of nanoparticles of homogeneously alloyed Ag and Pt, fabricated by a galvanic exchange of Pt with Ag. Importantly, these two elements were proven to have their own functionalities. Ag not only contributed to transporting e − and Had to the Pt for subsequent processes of the HER but also effectively extracted minority carriers by diluting the high work function of Pt, leading to a better Schottky barrier at the catalyst–insulator–semiconductor junction. Furthermore, computational simulation revealed that the proposed catalyst pattern alleviated optical light loss with the increasing catalyst loading compared to the two-dimensional case. Owing to these effects, we could achieve 0.36 V ( vs. reversible hydrogen electrode) as an open circuit potential and the near maximum current density of planar p-type Si. The findings in this work suggests deeper insights that could support the design of catalysts for solar-fuel systems.